Dynamic force applied by weightlifters of different weight categories in competitive exercises technique - Іванов [Artem Ivanov], Артем Володимирович (Slobozhanskyi Herald of Science and Sport, 2013)
We have studied the peculiarities of dynamic force appliance to the barbell by the weightlifters of different gender and weight category groups in two stages of the Clean and Jerk – the phase of preliminary acceleration and the phase of final acceleration. We have found out that achievement of high sport result can be provided by two ways of barbell lift: by means of maximal force appliance either in the phase of preliminary acceleration or in the phase of final acceleration. In the lightweight categories the majority of athletes use the second way of barbell lift; however, in the heavyweight categories the first way is applied. Males mainly use the first way of barbell lift, while females – the second. The dynamic structure of competitive exercises technique is influenced not only by the value of weight load but also by weight category of athletes.